Photon-number squeezed light generation by multi-photon absorption - Ward, M; Schucan, G; Turner, K; Goodson, T; Donovan, K; Aitchison, J; Ironside, C; Fox, A; Ryan, J (IEEE, 1999)
The first observation of multiphoton absorption using an AlGaAs waveguide within which high intensities can be maintained over a long interaction length is presented. In this system, two photon absorption are investigated by using ultrashort laser pulses with photon energies above the half-bandgap, and three-photon absorption by using photon energies below the half-bandgap. This enables to compare the squeezing from these two mechanisms and find that results relate well to theory that predicts stronger squeezing by three photon absorption for a given nonlinear absorption.